Etude comparative de la qualité des oeufs de poule locale et DE souche industrielle (Estimation des corrélations phénotypiques) Année Universitaire - yalaoui, sihem (My University, 2020)
This study was carried out in the region of Mostaganem whose main objective is to highlight the characteristics of the external and internal quality of eggs from two strains of industrial laying hens. A total of 60 eggs, divided into 30 eggs from industrial and 30 eggs from local laying hends, were collected and analyzed. The results show that in terms of the proportions of the three components of the egg (shell, yolk, white), no significant difference (P≥0.05) was observed between the two studied genotypes. from one hand, in local hens, the estimate of the phenotypic correlations between the parameters of the eggs show that the three principal components of the eggs noted that endosperm displayed the strongest relationship to the weight of the whole egg (+0,87; P<0,01). From the other hand, the phenotypic correlations between the internal and external parameters of eggs of industrial stock vary between -0.03 and 0.93. So, the strongest negative correlation was noted between both of the form and the length of eggs 0,37 (P<0,05). Local poultry species are of particular interest not only in diversifying agricultural production and improving productivity, but also in developing sustainable agriculture in the context of current and future climate change.
Keywords: laying hens; genotypes; eggs; quality; and phenotypic correlations